The Influence Of Work Stress, Work-Life Balance, And Work Facilities On Employee Performance At PT Astra Internasional Tbk-Tso Binjai - Amelia Nadin Ananta; Darmilisani Darmilisani; Eli Delvi Yanti (Journal of Management, Economic, and Accounting, 2026)
This study aimed to analyze the effect of work stress, work–life balance, and work facilities on employee performance at PT Astra Internasional Tbk – TSO Binjai. The study employed a quantitative approach with an associative method. The research population consisted of 80 employees, with all 80 respondents included as the sample using a saturated sampling technique. Primary data were collected through questionnaire distribution and processed using SPSS version 24. Data analysis was conducted using multiple linear regression to examine the relationship between independent variables and the dependent variable. The results showed that work stress, work–life balance, and work facilities had a positive and significant effect on employee performance, both partially and simultaneously. The t-test results indicated significant values for work stress (t = 3.585; sig. = 0.001), work–life balance (t = 5.987; sig. = 0.000), and work facilities (t = 6.528; sig. = 0.000). The F-test results showed an F value of 357.730 with a significance value of 0.000. All proposed hypotheses were proven and accepted. Work facilities were identified as the most dominant variable influencing employee performance, with the highest regression coefficient and beta value of 0.436. The coefficient of determination (adjusted R²) was 0.931, indicating that 93.1% of the variation in employee performance could be explained by the three independent variables, while the remaining 6.9% was influenced by other variables not included in this research model. In addition, the strength of the relationship between the independent variables and the dependent variable was categorized as very strong, with a correlation coefficient (R) value of 0.966.